Calculated in Death : In Death #36 - Robb, J. D., 1950-; Ericksen, Susan (Grand Haven, Mich. : Brilliance Audio, 2012)
When Marta Dickenson, a well-off accountant and a beloved wife and mother, is murdered, Lieutenant Eve Dallas immerses herself in her billionaire husband Roarke's world of big business to discover who arranged a hit on an innocent woman.
Unabridged.
Compact discs.
Read by Susan Ericksen.
Keywords: Dallas, Eve (Fictitious character) -- Fiction; Policewomen -- New York (State) -- Fiction; Mystery fiction; Audiobooks